SYNTHESIS OF IN SITU FORMING HYDROGELS OF PNIPAAm- PHPMA-PNIPAAm TRIBLOCK-COPOLYMERS USING RAFT POLYMERIZATION AND THEIR EVALUATION AS NEW THERMOSENSITIVE DELIVERY SYSTEM AGENT - (:unkn) unknown (My University, 2012)
0

Temperature responsive triblock copolymers of poly(N-isopropylacrylamide)-poly(N-(-2hydroxypropyl)methacrylamide)-poly(N-isopropylacrylamide)(PNIPAAm-PHPMA-PNIPAAm) have been prepared in two steps via reversible addition fragmentation chain transfer (RAFT) polymerization using carboxyl terminated trithiocarbonate (S,S’-%LV Į Į¶-dimethyl-Į¶¶-acetic acid)-trithiocarbonate) as the RAFT agent. The result showed that the copolymerization of PNIPAAm and PHPMA was of living character, and the corresponding copolymer produced had temperature responsive properties in water. While the block length of the hydrophilic middle block was kept constant, two different lengths of PNIPAAm blocks were used in the synthesis of triblock copolymers. The thermo-sensitive aggregation of polymers in water was studied using LCST (lower critical solution temperature) and sol-gel-sol change. The copolymers formed gels in situ under physiological condition. LCST increased as the PNIPAAm content decreased due to decrease in hydrophobicity of triblock-copolymer. All rheological measurements were performed using temperature controlled oscillating rheometer. The dynamic viscoelastic properties of the polymer solutions; storage modulus (G’) and loss modulus (G’’) were recorded. Storage modulus of polymer increased with increasing temperature as common in viscoelastic hydrogels. Results indicated that the hydrophobic/ hydrophilic balance achieved by varying the amount of comonomers used during synthesis was an important parameter in controlling the transition temperature of macromers in solution and stability of resultant gels
Keywords: Farmakoloji ve Eczacılık